Herpes simplex virus 1 alpha regulatory protein ICP0 interacts with and stabilizes the cell cycle regulator cyclin D3. - Kawaguchi, Y (1997)
The herpes simplex virus 1 (HSV-1) infected-cell protein 0 (ICP0) has the characteristics of a promiscuous transactivator of genes introduced into cells by infection or transfection. To identify cellular proteins interacting with ICP0, we used a domain of exon II of ICP0 that is known to be crucial for regulatory function of the protein as bait in the yeast two-hybrid screen. Our results were as follows. (i) A cDNA in a positive yeast colony was found to encode cyclin D3, a cell cycle regulator of G1 phase. (ii) A purified chimeric protein consisting of glutathione S-transferase (GST) fused to cyclin D3 specifically formed complexes with ICP0 contained in HSV-1-infected cell lysate. (iii) To enhance the expression of cyclin D3, the gene was inserted into the viral genome and overexpressed in infected cells. The overexpressed cyclin D3 colocalized with ICP0 in nuclear structures characteristic of ND10 and which earlier have been reported to contain ICP0. (iv) The accumulation of cyclin D3 protein in Vero cells infected with an alpha0 deletion mutant was reduced relative to that of cells infected with wild-type virus or a recombinant virus in which the deleted alpha0 sequences were restored. (v) Lysates of Spodoptera frugiperda Sf9 cells doubly infected with baculoviruses genetically engineered to express cyclin D3 and cyclin-dependent kinase 4 (CDK4) phosphorylated GST fused to retinoblastoma protein (GST-pRb) but did not phosphorylate the GST-alpha0(20-241) or GST-alpha0(543-768) fusion protein or immunoprecipitated ICP0 proteins. Moreover, the chimeric GST-ICP0(exon II) protein shown to bind cyclin D3 had no effect on the activity of the kinase on GST-pRb when added to mixtures of lysates of Sf9 cells which coexpressed cyclin D3 and CDK4. These results indicate that ICP0 interacts with, colocalizes with, and stabilizes the cyclin D3 cell cycle regulator and does not affect its interaction with the cyclin-dependent kinase.